Sociodemographic variables determine the academic performance of adolescents - Pestana, Leonor (2017)
Problem Statement: It is important to have a holistic approach to student learning, sustained in a multidisciplinary approach, in which socio-demographic factors and lifestyles may relate to academic achievement. Research Question was which socio-demographic variables influence the school performance (study environment, study planning, study method, reading skills, motivation to study, overall school performance) of adolescents? We aimed to identify socio-demographic factors associated with academic performance of adolescents. A quantitative, cross sectional, descriptive, correlational, explanatory, retrospective study applied as research methods. Information collected by questionnaire of direct administration and school performance scale. Non-probabilistic convenience sample of 380 students of 7th, 8th and 9th years of education in the school year 2011/2012, from a 2nd and 3rd cycle Basic School of Viseu Municipality, Portugal. The best school performance in adolescents was associated with female gender (p<0.001); with age ≤ 12 years, (p<0.001); with adolescents whose parents have secondary or higher education (p=0.019). There was no relationship between school performance and socioeconomic status and area of residence. Conclusions: It was concluded that the socio-demographic variables, including gender, younger age and parental education are determinants of adolescent school performance.